The Switch from LIBOR to OIS Discounting - Kotálová, Magdalena; Stádník, Bohumil; Staniek, Dušan; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2016)
The main contribution of the diploma thesis is to give a comprehensive picture of the switch from LIBOR to OIS discounting. Prior to the global financial crisis, LIBOR (London Interbank Offered Rate) represented an approximation of the risk-free rate in the valuation of interest rate derivatives. The collapse of Lehman Brothers in 2008 resulted in sharp widening of the LIBOR-OIS spread, an indicator of the interbank market stress. Many derivative practitioners have become concerned about the choice of an appropriate risk-free rate. Traditional valuation approaches using LIBOR discounting have been reviewed. Meanwhile, the OIS (Overnight Indexed Swap) rate has become a better proxy for the risk-free rate, at least for collateralized or centrally cleared transactions. Firstly, the research aims to discover the divergences between LIBOR rates, popular pre-crisis proxies for the riskfree rate, and OIS rates, their post-crisis alternatives. Secondly, it covers the interbank lending market, and analyzes individual LIBOR-OIS spreads for the USD, EUR, GBP and CZK currency. Thirdly, it explores the transition to OIS discounting in connection with an influence on a wide spectrum of interest rate derivatives. Therefore, any potential effects are demonstrated on numerical valuation examples of interest rate swaps in the USD, EUR, and GBP currency. Finally, the diploma thesis addresses a topic of collateral management and clarifies different approaches using LIBOR or OIS rates for collateralized or non-collateralized transactions.
Vedoucí práce: Bohumil Stádník
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses